329 Supplementing Native Rumen Microorganisms Improves Feedlot Steer Digestive Health and Performance. (8th October 2021) - Yang, Fan; Embree, Jordan; Gilmore, Sean; Embree, Mallory
Abstract: The rumen microbiome functions as a synchronized entity that digests feed in order to provide nutrients for its host. High-concentrate diets destabilize the rumen microbiome by biasing the community towards microorganisms that readily ferment simple carbohydrates resulting in decreased pH, increased CO2, and an increased solvent concentration in the rumen content. This chemical shift interrupts rumen fermentation and can lead to the development of metabolic diseases that negatively impact animal performance. This study evaluated the benefit of a daily, in-feed microbial feed supplement (MFS; Magnius, Native Microbials Inc, San Diego, CA) containing three native rumen microbes (Chordicoccus ruminifurens ASCUSBF65, Prevotella albensis ASCUSBF41, and Succinivibrio dextrinosolvens ASCUSBF53) on commercial feedlot steer performance and rumen microbiome composition. The trial was conducted by HMS Veterinary Development in Reedley, CA using 200 steers in 20 pens over 109 days with a 2x2 factorial design (with and without step-up period x with and without MFS). The without step-up group was directly fed the finisher ration (94% concentrate, 0.95 Mcal/lb NEm), while the step-up group was adapted to the finisher ration over a period of 21 days. Rumen microbiome samples were collected via stomach tubing periodically throughout the trial. At the end of 109 days, the FCR of the animals receiving MFS were significantly lower than the control animals (7.67% improvement, P = 0.013) in the step-up group, although no significant differences were observed in ADG and DMI. No significant performance differences were observed in the group without a step-up (Table 1). The relationship between rumen pH, dissolved CO2, and the observed changes in the microbiome suggest a potential interplay between acetogenesis and methanogenesis where CO2 consuming bacteria may be important in improving rumen digestive health. Collectively, these results suggest that feeding native rumen microorganisms can improve rumen resilience and health of high-grain consuming cattle.